Carbapenem-resistant Pseudomonas aeruginosa in malaysia producing IMP-7 beta-lactamase. - Ho, Siaw Eng; Subramaniam, Geetha; Palasubramaniam, Selvi; Navaratnam, Parasakthi (American Society for Microbiology, 2002)
We have isolated and identified a carbapenem-resistant Pseudomonas aeruginosa strain from Malaysia that produces an IMP-7 metallo-beta-lactamase. This isolate showed high-level resistance to meropenem and imipenem, the MICs of which were 256 and 128 micro g/ml, respectively. Isoelectric focusing analyses revealed pI values of >9.0, 8.2, and 7.8, which indicated the possible presence of IMP and OXA. DNA sequencing confirmed the identity of the IMP-7 determinant.